What are the perceived added values and barriers of regulating long-term care in the home environment using a care network perspective: a qualitative study - Didi Verver; Annemiek Stoopendaal; Hanneke Merten; Paul Robben; Cordula Wagner (BMC, 2018)
Abstract Background Changes in Dutch policy towards long-term care led to the Dutch Health and Youth Care Inspectorate testing a regulatory framework focusing on care networks around older adults living independently. This regulatory activity involved all care providers and the older adults themselves. Methods Semi-structured interviews with the older adults, and focus groups with care providers and inspectors were used to assess the perceived added value of, and barriers to the framework. Results The positive elements of this framework were the involvement of the older adults in the regulatory activity, the focus of the framework on care networks and the open character of the conversations with the inspectors. However, applying the framework requires a substantial investment of time. Care providers often did not perceive themselves as being part of a care network around one person and they expressed concerns about financial and privacy issues when thinking in terms of care networks. Conclusions The experiences of the client were seen as important in regulating long-term care. Regulating care networks as a whole puts cooperation between care providers involved around one person on the agenda. However, barriers for this form of regulation were also perceived and, therefore, careful consideration when and how to regulate care networks is recommended.